The New Silence Trend for Businesses: Quiet Hiring - Güzin Kıyık Kıcır (İşletme Bilimi Dergisi)
The reactive tendencies in silence, which have recently come to the fore in the business world, bring about the development of different adaptation skills for employees, managers and businesses. This research aims to conceptually understand and question the phenomenon of quiet hiring, which entered the literature after the concepts of quiet quitting and quiet firing. The fact that there is not much research on this concept, which has recently started to find a place in the literature, adds originality value to the study. In this article, which is a case study, the issue is examined at the level of definition, theoretical basis, antecedents, consequences, interaction with related concepts and recommendations. The quiet hiring approach, which aims to evaluate the existing human resource potential without going outside the organization, is characterized as a brand new employment policy in human resource management. The concept reveals a flexible understanding that responds quickly to silence instead of a passive aggressive organizational culture against silent reactions. At the end of the conceptual review, it was seen that quiet hiring has the potential to be successful if all human resources processes in enterprises are redesigned according to the organizational structure and human resource potential. When the literature is examined, it is determined that there is a gap in terms of both qualitative and quantitative research. Therefore, new studies can be designed that can increase the comprehensibility of the subject and question its relations with different concepts. In future research, it is important to develop terminology related to the concept, shape the theoretical basis, develop scales and guide new future studies.